Direct determination of chromium in empty medicine capsules by tungsten coil atomic emission spectrometry - Goncalves, Daniel A. [UNESP]; Gu, Jiyan; Santos, Mirian C. dos [UNESP]; Jones, Bradley T.; Donati, George L. (Royal Soc Chemistry, 2015)
Tungsten coil atomic emission spectrometry (WCAES) is used to determine trace levels of Cr in medicine capsules. No sample preparation other than 10 min vortex mixing with HNO3 and H2O2 is required. Matrix decomposition is carried out directly on the atomizer to minimize matrix effects and improve precision and accuracy. The entire analysis takes less than 12 min per sample including sample preparation. The instrumental setup is based on a tungsten filament extracted from 150 W, 15 V microscope light bulbs, solid state power supply, fused silica lens, crossed Czerny-Turner spectrograph and a thermoelectrically-cooled charge-coupled device detector. The limits of detection (LOD) and quantification (LOQ) for Cr are 3 and 9 mu g L-1, which correspond to procedure LOD and LOQ of 0.4 and 1 mu g g(-1), respectively. These values allow for quantification at a level 28-fold lower than the maximum daily Cr intake from medicine and medicine formulations recommended by the United States Pharmacopeial Convention (USP). The procedure's linear dynamic range is between 3-100 mu g L-1, with a R-2 = 0.9992. It was applied to different empty medicine capsule samples and WCAES results were not significantly different from values found by inductively coupled plasma optical emission spectrometry (ICP OES) by applying a single-factor ANOVA test at the 95% confidence level (p > 0.05). The precision, calculated as %RSD, is between 5.2-7.4%. This is a simple, fast, efficient and potentially portable analytical procedure that may be used in quality control and regulation enforcement applications.